Pengaruh Kompetensi Pedagogik Guru dan Motivasi Belajar Terhadap Prestasi Belajar IPS Siswa SDN Gugus 1 Kecamatan Walea Besar Kabupaten Tojo Una-una - Taufik; Kaluge, Laurens; Fauzia Putra, Dwi (Jurnal Penelitian dan Pendidikan IPS, 2023)
This study aims to determine and analyze the influence of teacher pedagogic competence on learning achievement, the influence of learning motivation on learning achievement, and the influence together of the influence of teacher pedagogic competence and learning motivation on the learning achievement of social studies subjects of SDN Cluster 1 Walea Besar District, Tojo Una-una Regency. This study uses a quantitative approach with a correlational descriptive design. The population in this study was all students of SDN Cluster 1, Walea Besar District, Tojo Una-una Regency, as many as 362 students. The sampling technique uses cluster sampling technique with a total of 80 students in grades IV, V, and VI of SDN 1 Supply. The data collection method uses questionnaires and documents, while the questionnaires are tested simultaneously with research samples with validity and reliability tests. Based on the results of the data analysis obtained, this study found that there is an influence of teacher pedagogic competence on student learning achievement. This is evidenced by the value for the teacher's pedagogical competence variable (X1) in the Sig column. is 0.000 less than alpha 0.05 and the calculated value is greater than the ttable at the 5% significance level of 12.932 > 1.664. There is an influence of learning motivation on student learning achievement. This is evidenced by the value for the variable pedagogical competence of the learning teacher (X2) in the Sig column. is 0.000 less than alpha 0.05 or the calculated value greater than ttable i.e. 10.258 > 1.664. There is no influence of teacher pedagogic competence and motivation to learn together on student learning achievement. This is evidenced by the sig column. is 0.816 more than alpha 0.05.